2021
DOI: 10.1038/s41587-020-00781-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting herpes simplex virus with CRISPR–Cas9 cures herpetic stromal keratitis in mice

Abstract: Herpes simplex virus type 1 (HSV-1) is a leading cause of infectious blindness. Current treatments for HSV-1 do not eliminate the virus from the site of infection or latent reservoirs in the trigeminal ganglia. Here, we target HSV-1 genomes directly using mRNA-carrying lentiviral particles that simultaneously deliver SpCas9 mRNA and viral gene-targeting gRNAs (designated HSV-1-erasing lentiviral particles, HELP). We show that HELP efficiently blocks HSV-1 replication and the occurrence of herpetic stromal kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 50 publications
5
99
0
Order By: Relevance
“…CRISPR/Cas9, besides being a versatile tool for research, also holds promising therapeutic potential for the treatment of persistent virus infections, as illustrated by the application to excise the integrated SIV genome in vivo [46,47]. Additionally, several studies showed successful targeting of herpesvirus genomes with either CRISPR/Cas9 or other programmable endonucleases, such as reducing latent EBV [14,48], latent KSHV [49], quiescent and latent HSV-1 genomes in vitro and in vivo [13,50] and, importantly, reducing herpes keratitis occurrence in vivo [23]. In this study, we showed that in vitro editing of VZV genomes during lytic infection is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR/Cas9, besides being a versatile tool for research, also holds promising therapeutic potential for the treatment of persistent virus infections, as illustrated by the application to excise the integrated SIV genome in vivo [46,47]. Additionally, several studies showed successful targeting of herpesvirus genomes with either CRISPR/Cas9 or other programmable endonucleases, such as reducing latent EBV [14,48], latent KSHV [49], quiescent and latent HSV-1 genomes in vitro and in vivo [13,50] and, importantly, reducing herpes keratitis occurrence in vivo [23]. In this study, we showed that in vitro editing of VZV genomes during lytic infection is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…2.12. Reconstitution of pOka-VLTM1I and pOka-VLTM1IR Viruses from BAC Genomes VZV strain pOka-based VLTM1I and its repaired VLTM1IR recombinant viruses were reconstituted in MeWo cells by transfection of pOka-BACVLTM1I and pOka-BACVLTM1IR genomes using Lipofectamine2000 (Thermo Fisher Scientific) and the BAC cassette within the reconstituted viruses was subsequently removed in MeWo-Cre cells [23,24].…”
Section: Generation Of Bacterial Artificial Chromosome (Bac) Mutant and Repaired Genomes By Redα/β-mediated Linear Recombinationmentioning
confidence: 99%
“…1a) 26 . We have previously shown delivery of Cas9 mRNA with lentivirus-derived VLP mediated efficient genome editing in vivo in the different disease models 27,28 , however, it is unclear if VLP can serve as a vaccine platform. To package the full-length spike mRNA into VLPs, we inserted MS2 stem-loop repeats in its 3' terminus between the stop codon and the polyA signal.…”
Section: Design and Characterization Of Vlp-based Sars-cov-2 Mrna Vaccinementioning
confidence: 99%
“…Previous studies focused on the regulatory network in non-CNS macrophages but provided a limited understanding of the regulatory mechanism for the innate antiviral response in CNS. Herpes simplex virus type 1 (HSV-1) is the most common human neurotropic viruses, infection of which causes numerous diseases, including herpes simplex encephalitis (HSE) that has a high mortality rate if left untreated, and herpetic stromal keratitis (HSK) is the leading cause of infectious blindness 14 , 15 . Moreover, the close association between HSV-1 and Alzheimer's disease has been gradually recognized 16 , although the underlying mechanism remains obscure.…”
Section: Introductionmentioning
confidence: 99%